2019
DOI: 10.1016/j.stemcr.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonadhesive Alginate Hydrogels Support Growth of Pluripotent Stem Cell-Derived Intestinal Organoids

Abstract: SummaryHuman intestinal organoids (HIOs) represent a powerful system to study human development and are promising candidates for clinical translation as drug-screening tools or engineered tissue. Experimental control and clinical use of HIOs is limited by growth in expensive and poorly defined tumor-cell-derived extracellular matrices, prompting investigation of synthetic ECM-mimetics for HIO culture. Since HIOs possess an inner epithelium and outer mesenchyme, we hypothesized that adhesive cues provided by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
177
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 46 publications
2
177
0
Order By: Relevance
“…It has been demonstrated that several niche factors allow adult and developing human and murine intestinal epithelium to be cultured ex vivo as organoids (Capeling et al, 2019; Finkbeiner et al, 2015; Fordham et al, 2013; Hill et al, 2017; Kraiczy et al, 2017; Sato et al, 2009, 2011). These factors often include WNT and RSPO ligands, BMP/TGFβ antagonists and EGF, and are based on defined growth conditions that allow expansion of intestinal epithelium in vitro (Sato et al, 2009, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that several niche factors allow adult and developing human and murine intestinal epithelium to be cultured ex vivo as organoids (Capeling et al, 2019; Finkbeiner et al, 2015; Fordham et al, 2013; Hill et al, 2017; Kraiczy et al, 2017; Sato et al, 2009, 2011). These factors often include WNT and RSPO ligands, BMP/TGFβ antagonists and EGF, and are based on defined growth conditions that allow expansion of intestinal epithelium in vitro (Sato et al, 2009, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The stem cell niche within a tissue is required to regulate stem cell maintenance, self-renewal and differentiation (Scadden, 2006). The niche is made up of both physical and chemical cues, including the extracellular matrix (ECM), cell-cell contacts, growth factors and other small molecules such as metabolites (Capeling et al, 2019; Cruz-Acuña et al, 2017; Gjorevski et al, 2016). Understanding the niche within various tissues has been central to understanding how tissues are maintain homeostasis, and for understanding how disease may occur (Van de Wetering et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human intestinal organoids (HIOs) have been almost exclusively characterized following growth for several weeks in culture (Capeling et al, 2019; Finkbeiner et al, 2015b; Spence et al, 2010; Tsai et al, 2017). Through these analyses, various intestinal epithelial and mesenchymal populations have been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of laminin‐111 in fibrin‐based hydrogels can achieve analogous colony formation efficiency to that of the Matrigel in organoid culture. Although other hydrogels like alginate hydrogels can support the survival of intestinal organoids (Capeling et al, ), their abilities to generate well‐differentiated organoids are poorer possibly due to the lack of coupled RGD and additive laminin‐111.…”
Section: Biomaterials For Intestinal Organoid Culturementioning
confidence: 99%